Cassava wastewater (manipueira) treatment using a two-phase anaerobic biodigestor - BARANA,Ana Cláudia (2000)
A two-phase anaerobic biodigestor was employed in order to analyze methane production with different manipueira organic loading rates. The acidogenic phase was carried out in a batch process whereas the methanogenic in an up-flow anaerobic fixed bed reactor with continuous feeding. The organic loading rates varied from 0.33 up to 8.48g of Chemical Demand Oxygen (COD)/L.day. The highest content of methane, 80.9%, was obtained with organic loading rate of 0.33g and the lowest, 56.8%, with 8.48gCOD/L.d. The highest reduction of COD, 88.89%, was obtained with organic loading rate of 2.25g and the lowest, 54.95%, with 8.48gCOD/L.d. From these data it was possible to realize that anaerobic biodigestion can be managed in at least two ways, i.e., for energy production (methane) or for organic loading reduction. The organic loading rate should be calculated as part of the purpose of the treatment to be accomplished.